Intensive Outpatient Treatment of Pediatric Rumination Syndrome in the Era of Telemedicine. Issue 3 (28th July 2022) - Hawa, Kathryn; Lu, Peter L.; Holzmacher, Meghan; Wall, Jody; Bali, Neetu; Vaz, Karla; Yacob, Desale; Di Lorenzo, Carlo; Van Diest, Ashley Kroon
Abstract : Objectives: We have had success treating children with severe rumination syndrome using a multidisciplinary intensive outpatient program (IOP) involving multiple treatment sessions daily. During the coronavirus disease 2019 (COVID-19) pandemic, we temporarily transitioned care to telemedicine. The objective of this study is to compare outcomes of patients with rumination syndrome who completed IOP treatment in person versus by telemedicine. Methods: We performed a retrospective review of patients diagnosed with rumination syndrome who participated in IOP treatment from 2018 to 2020. Similar treatment sessions were performed involving medical and behavioral techniques provided by a multidisciplinary team during telemedicine visits. Families/patients were asked to complete a survey outlining their child's current rumination symptom severity and review the IOP. Results: We included 34 patients (79% F, median age 15 years, range 7–19 years) who completed IOP treatment. Twenty-six patients (76%) were treated in person and 8 patients (24%) by telemedicine. For patients treated in person, 76% (19/25) had improvement in symptoms while 16% (4/25) had complete resolution of symptoms. For patients treated by telemedicine, 88% (7/8) had improvement in their symptoms. There were no significant differences between groups in likelihood of improvement. Overall, 78% (18/23) preferred in person therapy while 17% (4/23) did not have a preference. All 18 of the in-person cohort who completed follow-up surveys preferred in-person management. Conclusions: Multidisciplinary intensive outpatient treatment for children and adolescents with severe rumination syndrome is effective. Although telemedicine may be an alternative to in person therapy, majority of families prefer in person visits.